2022
DOI: 10.1364/ao.453344
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed laser source digital holography efficiency measurements

Abstract: In this paper, a 1064 nm pulsed laser source and a short-wave IR (SWIR) camera are used to measure the total system efficiency associated with a digital holography system in the off-axis image plane recording geometry. At a zero path-length difference between the signal and reference pulses, the measured total system efficiency (15.9%) is consistent with that previously obtained with a 532 nm continuous-wave laser source and a visible camera [Appl. Opt. 58, G19 (2019)APOPAI0003-693510.1364/AO.58.000G19]. In ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(33 citation statements)
references
References 33 publications
1
30
1
Order By: Relevance
“…To this end, the effect of temporal delay between the reference and signal pulses was recently studied using a 1064-nm pulsed laser source and a short-wave infrared (SWIR) camera. 18 These experiments showed that the measured total-system efficiency was comparable to that of a DH system in a CW configuration. It also introduced a novel component efficiency, called the ambiguity efficiency, to capture the effects of reduced pulse overlap.…”
Section: Introductionmentioning
confidence: 84%
See 4 more Smart Citations
“…To this end, the effect of temporal delay between the reference and signal pulses was recently studied using a 1064-nm pulsed laser source and a short-wave infrared (SWIR) camera. 18 These experiments showed that the measured total-system efficiency was comparable to that of a DH system in a CW configuration. It also introduced a novel component efficiency, called the ambiguity efficiency, to capture the effects of reduced pulse overlap.…”
Section: Introductionmentioning
confidence: 84%
“…( 1). Both efficiencies are described in detail elsewhere 13,16,18 and are not of primary concern in this paper. The mixing efficiency, however, merits additional consideration, since it quantifies of how well the reference and signal pulses interfere.…”
Section: Theorymentioning
confidence: 99%
See 3 more Smart Citations